The list:a short story and theoretical discussion of the issues involved in constructing adolescent and childhood voices in literature - Williams, Michael (My University, 2006)
Unable to copy the Abstract
Student No:990801j Faculty:Humanities Degree:MA
Keywords: Childhood voices in literature